How we remember what we can do - Declerck, Gunnar (Socioaffect Neurosci Psychol, 2015)
According to the motor simulation theory, the knowledge we possess of what we can do is based on simulation mechanisms triggered by an off-line activation of the brain areas involved in motor control. Action capabilities memory does not work by storing some content, but consists in the capacity, rooted in sensory-motor systems, to reenact off-line action sequences exhibiting the range of our powers. In this paper, I present several arguments from cognitive neuropsychology, but also first-person analysis of experience, against this hypothesis. The claim that perceptual access to affordances is mediated by motor simulation processes rests on a misunderstanding of what affordances are, and comes up against a computational reality principle. Motor simulation cannot provide access to affordances because (i) the affordances we are aware of at each moment are too many for their realization to be simulated by the brain and (ii) affordances are not equivalent to currently or personally feasible actions. The explanatory significance of the simulation theory must then be revised downwards compared to what is claimed by most of its advocates. One additional challenge is to determine the prerequisite, in terms of cognitive processing, for the motor simulation mechanisms to work. To overcome the limitations of the simulation theory, I propose a new approach: the direct content specification hypothesis. This hypothesis states that, at least for the most basic actions of our behavioral repertoire, the action possibilities we are aware of through perception are directly specified by perceptual variables characterizing the content of our experience. The cognitive system responsible for the perception of action possibilities is consequently far more direct, in terms of cognitive processing, than what is stated by the simulation theory. To support this hypothesis I review evidence from current neuropsychological research, in particular data suggesting a phenomenon of ‘fossilization’ of affordances. Fossilization can be defined as a gap between the capacities that are treated as available by the cognitive system and the capacities this system really has at its disposal. These considerations do not mean that motor simulation cannot contribute to explain how we gain perceptual knowledge of what we can do based on the memory of our past performances. However, when precisely motor simulation plays a role and what it is for exactly currently remain largely unknown.